ANALISIS DAN PENERAPAN METODE MULTIFACTOR EVALUATION PROCESS (MFEP) DALAM MENENTUKAN BIBIT TANAMAN BUNCIS YANG LAYAK UNTUK DIBUDIDAYAKAN - Ramadhan, Muhammad Hari; Yusfrizal, Yusfrizal (STMIK KAPUTAMA, 2019)
In planting plants, especially in beans, it is very necessary to select superior plant seeds. Beans as one type of vegetable that has a fairly complete nutritional content, including among them are sources of carbon and protein. Thus beans are very important to meet the needs of vegetable protein. Beans are one type of leguminous plant that has many uses. As a vegetable ingredient, bean pods can be consumed in a young condition or consumed by seeds. In this case, especially the farmers who are still beginners must be able to choose the seeds that are superior in cultivating the beans. And by utilizing the Decision Making Concept as well as the Application of the Multifactor Evaluation Process (MFEP) Method it is possible to help the novice farmer in determining the Bean Seeds that are Worth Cultivating.